Reflections on the treatment of the notions of control of the crime and joint criminal enterprise in the Staki? appeal judgement (2007)
One of the areas of international criminal law that has experienced a deeper evolution in the last decade is that of the applicable modes of liability other than superior responsibility. This evolution has been, to an important extent, the result of moving away from cases where the accused is a physical or low-level perpetrator, such as the Tadic case in the International Criminal Tribunal for the former Yugoslavia (“ICTY”) or the Akayesu case in the International Criminal Tribunal for Rwanda (“ICTR”). In this context, the Stakic´ Trial Judgement1 constituted a landmark decision insofar as it resorted for the first time in the jurisprudence of the ICTY to the notion of control of the crime. It did so with the aim to overcome some of the shortcomings of the traditional notion of joint criminal enterprise in cases against high ranking politicians and military leaders. Hence, the judgement of the Appeals Chamber in the Stakic´ case was very much expected insofar as it was supposed to deal with the issue of whether the notion of control of the crime is part of the applicable law before the ICTY.